Determinants of Coffee Experts of Bandar Lampung Province in the International Market for the Period 2004-2022 - Maulida, Safia; Hafidh Saiful Fikri, Aula Ahmad (Riviera Publishing, 2023)
This research aims to analyze the influence of Bandar Lampung province's coffee exports in the long and short term and analyze the competitiveness of coffee in the international market. This research is research with a quantitative approach. The data collection technique uses time series data totaling 70 quarters. The analysis technique uses the Error Correction Model (ECM) with prerequisite tests, namely the classical assumption test, stationarity test, cointegration test, ECM test, ECT test, and analysis. Revealed Comparative Advantage (RCA). Research findings show that 1) the rupiah exchange rate influences coffee exports in the long and short term. 2) There is an influence of production on coffee exports in the long and short term. 3) International coffee prices influence coffee exports in the long and short term. 4) Domestic coffee prices influence coffee exports in the long and short term. 5) There is a simultaneous influence of the rupiah exchange rate, production, international coffee prices, and domestic coffee prices on coffee exports, namely 74 percent. 6) The competitiveness of coffee in the international market has a comparative advantage of R>1. The research implies the importance of exchange rate policies, management of production and exports, as well as comparative advantage in international market competition. Continuous improvement in the quality and competitiveness of coffee is crucial for maximizing this potential in the global market.